Students Programme Satisfaction and Loyalty towards Their Departments and Institutions - , Ismail Olaniyi Muraina (Archives of Current Research International, 2018)
Delivering a high level of educational quality is important as a means of getting satisfied and contended with the services rendering by the school or department to maintain loyalty with such school or department. The study looks at the students' programme satisfaction and loyalty towards computer science department in Adeniran Ogunsanya College of Education. Sixty students were sampled randomly. 200 level and 300 level students were made up the population, with the exemption of 100 level because they were new to the system. A questionnaire was used to collect data. Structural Equation Modeling (SEM) using SmartPLS 3.0 was used to analyze the data collected. It was found that student programme perceived quality has the great effect on student programme satisfaction; student programme satisfaction is a good predictor of student loyalty to computer science. Institutions need to make it point of duty to provide an avenue for students to get what they want from their various schools or departments and to make students satisfied and loyal to their institutions. The limitation of this study includes failure to bring out the rate at which a student should be loyal to his/her department/Institution to know that such student is satisfied with the programme and how to rate the student’s satisfaction to the department/Institution.